Physical and chemical properties of blood in patients with reactive chlamydia arthritis with oculopathia - А. K. Pavlyuchenko; L. V. Lukashenko; O. V. Syniachenko (Zaporožskij Medicinskij Žurnal)
Reactive chlamydia arthritis is accompanied by the increase of parameters of volume viscidity, elastic of viscidity and static (equilibrium) surface-tension and phase corner of tensiogramm serum of blood, on background of the reduction of relaxation time, that is related with duration of illness, activity of pathological process, tendovaginities. Major role in the development of oculopathy (uveitis, scleritis, keratitis, conjunctivitis, cataract, glaucoma) take part disorders of the adsorption-rheological properties of the blood.